Vietnam Development Report 2004 : Poverty - World Bank (Washington, DC, 2013)
Progress in Vietnam has been substantial when other dimensions of poverty, apart from expenditures, are considered. The broader Vietnam Development Goals (VDGs), which are a localized version of the Millennium Development Goals, show a consistent improvement of social indicators, from education enrollment to infant mortality. While some regions and some population groups gained more than others, Vietnam continues to reduce poverty considerably faster than other countries at a similar development level. In the early 1990s, its poverty rate was higher than could be expected, given the country's level of economic development. Some time during the second half of the 1990s Vietnam caught up with the "average" country at its development level, and it largely surpassed it by 2002. The "story" behind the reduction in poverty has somewhat changed over time. Earlier gains had been associated with the distribution of agricultural land to rural households, in a context where economic reform provided the right incentives for increased farm production. But those gains have been mainly reaped by now. In more recent years, the driving forces behind poverty reduction are job creation by the private sector and the increased integration of agriculture in the market economy. A vast majority of the working-age population of Vietnam actually works, and labor market participation rates are among the highest in the world. What has changed is not activity, but rather the composition of employment. Over the last four years, the proportion of people who mainly work on their own farm dropped from almost two thirds to slightly less than half. Instead, many more are now engaged in wage employment: 30 percent of those at work earned a wage in 2002, compared to 19 percent four years earlier. Thanks to its buoyant expansion, by 2002 the formal private sector already accounted for around 2.5 million jobs, more than the entire public sector. But a much larger number of jobs have been created by the private informal sector.